(untitled) (Per Musi, 2017)
This paper aims to expand on previous considerations on the approach poetical and musical categories of wit and stravaganza of the 1600s. Both are considered as expression of bizzarria, the relation between them will be clarified by the concept of mimesis and its unfoldings when confronted with the notion of phantasia. All these relations come to light from two sources: first, the theological allegory from Latin medieval rhetoric; second, the concession to non-verisimilar from Hellenistic Byzantine rhetoric.